Exploring Coffee Preferences: An Analysis of Consumption Trends among University Students in Costa Rica - Hunter, Roberto; Jiménez Marín, Victor Emilio; Berlioz Pastor, José Guillermo; Chang, Raúl Javier (LACCEI, 2024)
Caffeine is widely consumed among students due to its cognitive and physical enhancing effects. However, little is known about the consumption pattern of different caffeinated products among university students in Costa Rica. Data collection involved administering a questionnaire intended to measure students' coffee drinking preferences. To carry out this study, a sample of university students from the Universidad Latina of Costa Rica was selected. Furthermore, it should be noted that a significant percentage of people abstain from coffee consumption. Reasons for abstaining include loss of taste for coffee or concern about its impact on health. Interestingly, about a third of participants have little knowledge about medical products containing caffeine, which seemed to affect the level of consumption in the student population. The results of the research lead us to determine the evolution of consumer priorities, especially university students, with respect to coffee consumption. The emphasis on flavor and atmosphere as the most important factors (51.15% and 48.84 respectively) underlines the importance of creating a sensory experience in coffee consumption.